Konsep Scaffolding dalam Perspektif Pendidikan Islam: Analisis Pemikiran Ibnu Khaldun dan Vygotsky - Imraatul hasanah; Asmaul Husna; Hepi Ikmal; Ach. Sayyi (Akademika, 2025)
This study aims to analyze and integrate the concept of scaffolding within the framework of Islamic education by examining the thoughts of Ibn Khaldun and the constructivist theory of Lev Vygotsky. Amidst global educational challenges and the growing need for adaptive and contextual learning approaches, scaffolding emerges as an effective pedagogical strategy to support students' optimal cognitive development. Vygotsky, through his concept of the Zone of Proximal Development (ZPD), underscores the importance of external assistance from teachers or more knowledgeable others in the learning process. Meanwhile, Ibn Khaldun, in his seminal work Muqaddimah, emphasizes the necessity of gradual instruction (tadarruj), repetition, and the psychological readiness of learners in acquiring knowledge. This study employs a qualitative-descriptive approach with a library research design. Data were analyzed through content analysis of both primary and secondary sources relevant to the topic. The findings reveal a conceptual convergence between Vygotsky's scaffolding and Ibn Khaldun's educational philosophy, particularly in the teacher's role as a facilitator and the importance of tailored learning support based on students’ capabilities. The novelty of this research lies in its integrative effort to construct a conceptual bridge between classical Islamic thought and modern educational theory. Furthermore, it offers practical contributions as a foundation for developing Islamic learning models grounded in values and contextual relevance. This study is expected to serve as a reference for progressive and localized pedagogical renewal in Islamic education.